A Comparative Study on Self Compassion among Parents of Children with Intellectual Disability and Deafblindness - Dr. Simi Shrivastava; Mr. Pankaj Kumar Maurya (International Journal of Indian Psychȯlogy, 2025)
A disability is a physical, sensory, cognitive, or developmental impairment that limits an individual’s ability to perform daily activities in society. Intellectual disability (ID) is a neurodevelopmental disorder characterized by limitations in intellectual functioning and adaptive behaviour. Deafblindness refers to a combined vision and hearing impairment that significantly impacts an individual’s ability to communicate, access information, and navigate their environment. Parents of children with intellectual disabilities and deafblindness often face unique challenges that can have a significant impact on the family dynamics and functioning. Parenting stress has a profoundly negative impact on parental behaviours and, consequently, can seriously affect children’s emotional, social, and cognitive development.  It is important to understand ways of supporting parents and families with individuals with IDD. One important but most negligible factor which can better understand the needs of parents and also help parents to cope their challenging stress is – Self Compassion.  Self-compassion is the practice of treating oneself with kindness, understanding, and acceptance, especially during times of difficulty or failure. Self-compassion is a potential internal coping resource for parents, and is strongly linked to positive mental health outcomes. The present study is to find out the self compassion level among parents of intellectual disability and parents of children with deafblindness. A total of 68 parents were selected for this study. The results revealed that although both the groups of parents were facing the same concern of taking care of their special children but their self compassion levels were found to be at a moderate level. There are some significant differences found among both the groups of parents in the main components of Self compassion level. This kind of a result indicates that irrespective of having children with special needs; the parents are alert, aware about their children’s development which is affecting at a moderate level with respect to their self compassion. Hence with proper support, guidance and through parent training programs the self compassion level can be improved and be more accepting and effective.